2003
DOI: 10.1073/pnas.2336131100
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of RNA editing by functional nucleolar sequestration of ADAR2

Abstract: The adenosine deaminases that act on RNA (ADARs) catalyze the site-specific conversion of adenosine to inosine (A to I) in primary mRNA transcripts, thereby affecting the splicing pattern or coding potential of mature mRNAs. Although the subnuclear localization of A-to-I editing has not been precisely defined, ADARs have been shown to act before splicing, suggesting that they function near nucleoplasmic sites of transcription. Here we demonstrate that ADAR2, a member of the vertebrate ADAR family, is concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
177
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(188 citation statements)
references
References 59 publications
11
177
0
Order By: Relevance
“…Transfection of eGFP alone resulted in a diffuse pattern of fluorescence in the cytoplasm and nucleus, with no preferential concentration in nucleoli, whereas the pattern of eYFP-nucleolin fluorescence was highly restricted to the nucleolar compartment (Figure 2A). The fluorescence pattern for cells cotransfected with both eGFP and eYFP-nucleolin was identical to that observed when each fluorophore was transfected independently, with little observable bleedthrough between the emission channels for these simultaneously excited fluorescent proteins (Figure 2A).Transient expression of wild-type eGFP-ADAR2 in NIH/ 3T3 cells demonstrated the previously observed pattern of nucleolar localization (Fn/Fo ϭ 13.8 Ϯ 2.4), and deletion of both dsRBM domains and the intervening 81-aa linker [⌬dsRBM1/2 (⌬76 -301)] produced the expected pattern of diffuse nuclear fluorescence (Figure 2A), suggesting that dsRNA binding was required to maintain the steady-state localization of ADAR2 in nucleoli (Desterro et al, 2003;Sansam et al, 2003). Expression of a mutant eGFP-ADAR2 fusion protein (K127A, K281A), containing substitutions for highly conserved amino acids in the loop between the ␤3 and ␣2 regions for all dsRBMs (Tian et al, 2004), resulted in a diffuse pattern of nuclear fluorescence nearly identical to the pattern observed when the region containing both dsRBMs was deleted from the fusion protein (Figure 2A).…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Transfection of eGFP alone resulted in a diffuse pattern of fluorescence in the cytoplasm and nucleus, with no preferential concentration in nucleoli, whereas the pattern of eYFP-nucleolin fluorescence was highly restricted to the nucleolar compartment (Figure 2A). The fluorescence pattern for cells cotransfected with both eGFP and eYFP-nucleolin was identical to that observed when each fluorophore was transfected independently, with little observable bleedthrough between the emission channels for these simultaneously excited fluorescent proteins (Figure 2A).Transient expression of wild-type eGFP-ADAR2 in NIH/ 3T3 cells demonstrated the previously observed pattern of nucleolar localization (Fn/Fo ϭ 13.8 Ϯ 2.4), and deletion of both dsRBM domains and the intervening 81-aa linker [⌬dsRBM1/2 (⌬76 -301)] produced the expected pattern of diffuse nuclear fluorescence (Figure 2A), suggesting that dsRNA binding was required to maintain the steady-state localization of ADAR2 in nucleoli (Desterro et al, 2003;Sansam et al, 2003). Expression of a mutant eGFP-ADAR2 fusion protein (K127A, K281A), containing substitutions for highly conserved amino acids in the loop between the ␤3 and ␣2 regions for all dsRBMs (Tian et al, 2004), resulted in a diffuse pattern of nuclear fluorescence nearly identical to the pattern observed when the region containing both dsRBMs was deleted from the fusion protein (Figure 2A).…”
supporting
confidence: 75%
“…These disadvantages include differences in the levels of expression for transfected fusion proteins and minigene-derived RNA substrates and the fact that such cellular RNA processing events do not necessarily occur in the linear range for ADAR2 enzymatic activity. In addition, previous studies have demonstrated that A-to-I conversion takes place in the nucleoplasm (Rueter et al, 1999;Raitskin et al, 2001;Desterro et al, 2003;Sansam et al, 2003) and that translocation of ADAR2 to the nucleoplasm results in increased editing activity (Sansam et al, 2003), making comparisons of editing activity for mutations that simultaneously affect both subnuclear accumulation and site-specific editing difficult to interpret.To circumvent these problems, we used an in vitro editing system using crude nuclear extracts from HEK293 cells transiently transfected with different eGFP-ADAR2 mutants. The relative protein level for wild-type and mutant eGFP-ADAR2 proteins in HEK293 nuclear extracts was determined by quantitative Western blotting analysis using an affinity-purified antiserum directed against amino acids 6 -66 of wild-type ADAR2 (Figure 4) (Sansam et al, 2003;Dawson et al, 2004), and all proteins were diluted to achieve the same final concentration in the in vitro editing reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ADAR2 localizes predominantly in the nucleolus 44,46 . The significance of the nucleolar localization of ADAR1S and ADAR2 is not currently clear.…”
Section: Adar Gene Expression and Regulationmentioning
confidence: 99%
“…Thus, many non-traditional functions of the nucleolus have been proposed [5][6][7]9]. These include signal recognition particle assembly, small RNA modification, RNA editing, telomerase maturation, nuclear export, cell cycle control, and stress sensor [17][18][19][20][21][22]. The nucleolar proteins unrelated to ribosome assembly mostly contain an RNA-binding motif or have a chaperone function.…”
Section: Plurifunctionality Of the Nucleolusmentioning
confidence: 99%